Some new combinatorial algorithms with appropriate representations of solutions - Hoang, Chi Thanh (H. : ĐHQGHN, 2017)
Combinatorial problems are those problems, whose requirements are an association of some conditions. The construction of efficient algorithms to find solutions of the combinatorial problems is still an interesting matter. In this paper, we choose appropriate representations for desirable solutions of the permutation problem and the partition problem. Then we sort the representations of a problem's solutions in the alphabetical order. Owing to it we construct two new algorithms for quickly finding all solutions of these problems.